1997
DOI: 10.1007/bf02480366
|View full text |Cite
|
Sign up to set email alerts
|

Channel blocking drugs as tools to study glutamate receptors in insect muscles and molluscan neurons

Abstract: The action of three dicationic drugs, derivatives of adamantane (IEM-1460 and IEM-1754) and phencyclidine (IEM-1925), on glutamate receptors (GluRs) at the insect neuromuscular junction (Calliphora vicina larva) and on neurons of the freshwater gastropodian mollusc Planorbarius corneus has been studied using the voltage clamp technique. In the presence of concanavalin A complex glutamate-induced currents recorded from molluscan neurons reflected mainly the opening of cationic channels as a result of decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The dicationic adamantane derivatives IEM‐1754 and IEM‐1460 are potent blockers of open channels of native ionotropic glutamate receptors including quisqualate‐sensitive receptors in insect muscles (Magazanik et al ., 1984; Samoilova et al ., 1997), NMDAR in cultured rat cortical neurones (Antonov et al ., 1995) and AMPAR in freshly isolated hippocampal cells (Magazanik et al ., 1997). In the latter case, the potencies of these compounds depend on the cell type studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dicationic adamantane derivatives IEM‐1754 and IEM‐1460 are potent blockers of open channels of native ionotropic glutamate receptors including quisqualate‐sensitive receptors in insect muscles (Magazanik et al ., 1984; Samoilova et al ., 1997), NMDAR in cultured rat cortical neurones (Antonov et al ., 1995) and AMPAR in freshly isolated hippocampal cells (Magazanik et al ., 1997). In the latter case, the potencies of these compounds depend on the cell type studied.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical structures of these compounds are shown in Figure 1. IEM‐1925, like IEM‐1460 and IEM‐1754, reversibly blocks ion channels of ionotropic glutamate receptors of insect muscles and mollusc neurones (Samoilova et al ., 1997). The studies reported herein have been performed on visually identified pyramidal and nonpyramidal cells isolated from rat hippocampal slices without enzymatic treatment.…”
Section: Introductionmentioning
confidence: 99%
“…This action of IEM-1925 on movement disorders in mice may be associated with its high blocking activity not only in relation to NMDA receptors, but also against other glutamate receptor subtypes [11]. The roles of AMPA and kainate receptors in the genesis of movement disorders remain to be clarified in future studies.…”
Section: Resultsmentioning
confidence: 97%
“…This will improve understanding of the pathways of the molecular evolution of ion channels and membrane receptors, and will also aid in solving applied problems, especially that of creating new substances which are toxic to invertebrates but harmless to humans and vertebrate animals. Adamantane derivatives have been found to block glutamate-activated cation-selective ion channels in mollusk neurons [6,44] and insect muscles [2,3]. The mechanisms of blockade, however, are similar to previously studied mechanisms of inhibition of AMPA receptors, since the presence of agonist is essential for blockade and the level of blockade depends on the membrane potential in vertebrate cells [44].…”
Section: Channel Blockers As Tools For Studies Of Glutamate Receptorsmentioning
confidence: 92%
“…Adamantane derivatives have been found to block glutamate-activated cation-selective ion channels in mollusk neurons [6,44] and insect muscles [2,3]. The mechanisms of blockade, however, are similar to previously studied mechanisms of inhibition of AMPA receptors, since the presence of agonist is essential for blockade and the level of blockade depends on the membrane potential in vertebrate cells [44]. Thus, blockade of open ion channels can be included in a set of methods used for identifying the similarities and differences between ionotropic receptors of vertebrates and invertebrates.…”
Section: Channel Blockers As Tools For Studies Of Glutamate Receptorsmentioning
confidence: 99%